Penyuluhan Penyakit Tidak Menular (PTM) Untuk Menumbuhkan Kesadaran Pencegahan Pada Masyarakat Menggunakan Aplikasi GEMPITA Di Wilayah Karang Jati, Balikpapan - Ridhwan Haliq; Andi Idhil Ismail; Muchammad Jamil; Alfian Djafar; Kholiq Deliasgarin Radyantho; Faisal Manta (CV. Multi Kreasi Media, 2024)
Noncommunicable diseases (NCDs) are common in Indonesia; this is also true in Karang Jati, Balikpapan, and East Borneo. Despite this, the villagers have little knowledge about prevention, despite being aware of the grave consequences that diseases can have on their well-being and social standing. This exercise aims to raise villagers' understanding of the need to prevent non-communicable diseases. Using NCD screening with information distribution, this activity has encouraged the villagers to become more aware of the condition and motivated them to take preventative action. Most of the villagers are at high risk of noncommunicable diseases (NCDs), specifically hypertension, according to the screening results. These data have effectively supported the villagers in establishing NCD screening and management in their neighborhood through Pos Pembinaan Terpadu (Posbindu) PTM, a community-based NCD prevention and management activity.